Physical Characteristics, Total Flavonoids, Total Phenols and Antioxidant Activity of Ketepeng Cina Leaf Herbal Tea (Cassia Alata L.) - Intan Sari, Febby; Julianti, Elisa; Romauli, Nauas Domu Marihot (Eduvest - Journal of Universal Studies, 2025)
Ketepeng cina leaf herbal tea is a functional beverage made from the dried leaves of Cassia alata (ketepeng cina), which are known to contain beneficial bioactive compounds. However, its use as a herbal drink remains limited. This study aimed to investigate the effects of stevia leaf addition (0%, 6%, 12%, and 18%) and brewing time (2, 3, and 4 minutes) on the physicochemical and sensory characteristics of ketepeng cina leaf herbal tea. A completely randomized design (CRD) with a two-factor factorial pattern and three replications was employed. The parameters evaluated included color index, pH, total soluble solids (TSS), total flavonoids, total phenols, antioxidant activity, and sensory attributes. Data were analyzed using ANOVA at a 5% significance level, followed by Duncan’s Multiple Range Test (DMRT) when significant differences were found. The findings showed that stevia concentration and brewing time significantly influenced the tea's characteristics. The optimal formulation was achieved with an 18% stevia concentration and a 3-minute brewing time, resulting in 3.68°Brix TSS, 0.18 mgQE/g total flavonoids, 1.93 mgGAE/g total phenols, and 49.21% antioxidant activity. This study suggests that the addition of stevia and controlled brewing time can improve the functional and sensory quality of ketepeng cina herbal tea, making it a promising alternative in the development of antioxidant-rich herbal beverages.